Factor Analysis Of Increasing Elderly Tourist Satisfaction At Bogor Botanical Garden - Apriyanti, Rehulina; Akhirson, Armaini; Angin, Rosliyana Perangin (International Journal of Artificial Intelligence Research, 2023)
This study aims to be able to find out the influence of the image of tourist destination locations, prices, and facilities in the tourist area in the Bogor Botanical Garden on the satisfaction of elderly tourists. This study uses quantitative analysis through several resistant tests, namely the validity test stage, reliability test stage, and classical assumption test stage (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis stage. The hypothesis test is to perform a t-test, an F-test, and a coefficient of determination. Data was collected by making questionnaires to be distributed to 100 respondents through random sampling and analysis using SPSS. The results of this study show that there are some of the destination image variables will greatly affect the satisfaction of elderly tourists in the Bogor Botanical Garden tourist area, where the price will affect the satisfaction of elderly tourists, and the existence of facilities in the Bogor Botanical Garden tourist area will affect the satisfaction of elderly tourists. So it can be concluded that the image of a tourist destination area, prices, and facilities will be able to affect the satisfaction of elderly tourists in the Bogor Botanical Garden tourist area.